2010
DOI: 10.2214/ajr.09.2845
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Input Function Placement for Accurate CT Perfusion Map Construction in Acute Stroke

Abstract: OBJECTIVE The objective of our study was to evaluate the effect of varying arterial input function (AIF) placement on the qualitative and quantitative CT perfusion parameters. MATERIALS AND METHODS Retrospective analysis of CT perfusion data was performed on 14 acute stroke patients with a proximal middle cerebral artery (MCA) clot. Cerebral blood flow (CBF), cerebral blood volume (CBV), and mean transit time (MTT) maps were constructed using a systematic method by varying only the AIF placement in four posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…79 These studies revealed no significant difference in the quantitative CTP data with AIF selection ipsilateral or contralateral to the side of MCA vessel occlusion in either the ACA or MCA segments. However, AIF selection distal to an embolus revealed significant differences in the quantitative CTP data recommending avoiding its placement.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…79 These studies revealed no significant difference in the quantitative CTP data with AIF selection ipsilateral or contralateral to the side of MCA vessel occlusion in either the ACA or MCA segments. However, AIF selection distal to an embolus revealed significant differences in the quantitative CTP data recommending avoiding its placement.…”
Section: Introductionmentioning
confidence: 82%
“…711 These studies found that major variations in the AIF location had no significant effect on the quantitative CTP data. 7,911 Additionally, the ACA and even the superficial temporal artery may be used as appropriate AIF locations in patients with acute stroke regardless of the cortical region affected which may assist in standardization of the AIF location. 7,911 Furthermore, there is no significant difference in the quantitative CTP data when selecting an AIF location in the MCA or ACA segments ipsilateral or contralateral to the vascular territory with infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial input function placement distal to an arterial thrombus, however, undermines perfusion calculation assumptions, and causes significant variability in CT perfusion results. 4 Two additional studies 9,19 found that varying placement of the venous output function caused significant variability in CT perfusion results. Although the anterior cerebral artery is commonly selected for the arterial input function and the superior sagittal sinus is commonly selected for the venous output function, there is no standard recommendation for selecting these user inputs.…”
mentioning
confidence: 99%
“…4,13,14,22 Different corrective functions for partial-volume effects (inaccurate measurements of contrast media concentration that occur due to the small size or location of cerebral vessels) cause significantly different CT perfusion results. 25 Computed tomography perfusion software that uses a corrective technique called vascular pixel elimination was found to more closely correlate with PET results than software that does not incorporate this technique.…”
mentioning
confidence: 99%